Impact of innovation platforms on marketing relationships: The case of Volta Basin integrated crop-livestock value chains in Ghana - Adane-Mariami, Z.; Cadilhon, Joseph J.; Werthmann, C. (2015)
Scientific and agricultural development approaches to improve the livelihoods of smallholder agriculturalists in developing countries are shifting from “linear transfer of technology models” towards “systems thinking”. One manifestation of this shift is the recognition of agricultural innovations as multidimensional and co-evolutionary processes that integrate technological, organisational, socio-economic and institutional innovations. This paper attempts to test a new conceptual framework for evaluating innovation platforms for agrifood value chains. The framework is based on the structure-conduct-performance hypothesis of industrial organisation, in combination with concepts of new institutional economics and marketing relationships. Data to test the framework was collected from two innovation platforms in the Volta2 Project in Ghana. Both the qualitative and quantitative data collected validate a possible link between the structure of the platforms, the conduct of their members and the resulting market performance through reducing the transaction costs of search and information.